Inorganic chemical components in precipitation in the eastern U.S. and Eastern Canada during 1989–2016: Temporal and regional trends of wet concentration and wet deposition from the NADP and CAPMoN measurements. (1st June 2021) - Feng, Jian; Vet, Robert; Cole, Amanda; Zhang, Leiming; Cheng, Irene; O'Brien, Jason; Macdonald, Anne-Marie
Abstract: With the implementation of the Clean Air Act Amendments of 1990 in the U.S. and similar emission reduction measures in Canada, sulfur dioxide (SO2 ) and nitrogen oxides (NOx  = NO + NO2 ) emissions in the eastern U.S. and Eastern Canada declined significantly during the period 1989–2016. Correspondingly, air quality over the region improved tremendously and sulfate, nitrate and acidity in precipitation decreased significantly. In this study, we analyzed measurement data in the eastern U.S. and Eastern Canada from the two national long-term wet deposition networks, the National Atmospheric Deposition Program/National Trends Network (NADP/NTN) in the U.S. and the Canadian Air and Precipitation Monitoring Network (CAPMoN) in Canada, to reveal the spatial-temporal trends of precipitation concentrations and wet deposition of sulfate, nitrate, ammonium and acid in the eastern part of North America (broken into 4 different regions) for the period of 1989–2016. Comparing 2014–2016 to 1989–1991, the results show that the acid, sulfate and nitrate wet deposition decreased by 78%, 69% and 46% for 1989–2016, and decreased annually at rates of −2.8~-3.6% yr −1, -2.5~-2.9% yr −1, and -1.6~-2.0% yr −1 over different regions, respectively. It also revealed that there were no statistically significant trends for the annual mean wet concentrations of ammonium (NH4 + ) in precipitation in the Midwest and the Mid-Atlantic of the U.S. ( P >0.4 respectively). However, there were statistically significant increasing trends of annual wet deposition of NH4 + over these latter two regions ( P  = 0.01–0.13) with an annual rate of increase of 0.6% and 0.4%, respectively. The increasing trends of wet deposition of NH4 + in these regions were mostly due to increasing annual precipitation amounts, as indicated by positive correlation coefficients between them ( R  = 0.67–0.77), and a statistically significant increasing trend of the precipitation amount during the period. The annual mean wet concentration of chloride ion (Cl − ) in precipitation in the above two regions had a clear decreasing trend of −1.5% annually ( P  < 0.001). In 20 years (2010–2014 vs . 1990–1994), the frequency of acidic rain with pH < 5 was reduced from 72% to 49% in the Northeast U.S. and Eastern Canada, 88% to 37% in the Midwest, 97% to 60% in the Mid-Atlantic and 79% to 49% in the Southeast. The imbalance between the measured cations and anions increased over the years from 2009 to 2016 with the anions dropping lower than the cations in all regions. This can be attributed to the increased dissociation of weak organic acids, i.e., the free H + contributed from these weak acids increased as the acidity of the precipitation decreased, but the corresponding conjugate bases were not measured and not included in the calculation of total anions. This pH buffering effect needs to be taken into account in assessing the reductions in acid deposition following the implementation of the Clear Air Act Amendments (CAAA) of 1990 in the U.S. and measures to reduce the emissions of SO2 and NOx in Canada. Highlights: A new statistical method was proposed to eliminate potential biases in deriving long-term trends. The trends derived with the proposed method are more robust than some previously published ones. Comparing 2014-2016 to 1989-1991, the acid, sulfate and nitrate wet deposition in the eastern U.S. and Eastern Canada decreased by 78%, 69% and 46% for 1989-2016, and decreased annually at rates of -2.8~-3.6% yr -1, -2.5~-2.9% yr -1, and -1.6~-2.0% yr -1 over different regions, respectively. The imbalance between measured cations and anions increased after 2009, and it was attributed to the increased dissociation of weak organic acids. The trends of the wet concentration of NH4 + remained flat when less H + was contributed from SO4 2- and NO3 -, as H + dissociated from carbonic acid and weak organic acids compensated for the loss of H + from SO4 2- and NO3 - in the formation of NH4 + in precipitation. An explanation was proposed for the lack of trends in the wet concentration of NH4 + during the study period. NHx (NHx  = NH3  + NH4 + ) was shown to have a flat trend for 2008–2016 in the Midwest despite the partitioning of NHx having changed with emission reductions of SO2 and NOx .